Substrate for Surface-Enhanced Raman Spectroscopy Formed by Gold Nanoparticles Buried in Poly(methyl methacrylate) - Gushiken, Natalia K. (ACS Omega, 2020)
[Image: see text] In this work, we present some properties and use of a nanocomposite formed by gold nanoparticles (NPs) into poly(methyl methacrylate) (PMMA) and its application as substrates for surface-enhanced Raman spectroscopy (SERS). The nanocomposite was formed using low-energy (49 eV) ion implantation of gold in PMMA using a cathodic arc plasma gun. The gold NPs are formed spontaneously from the implanted ions and they remain isolated from each other by the polymer medium surrounding them, ensuring a spacing between the NPs of less than 10 nm (hot spot places). The NPs form below the surface, protected from the environment, guaranteeing the stability of the composite layer. Moreover, here, we present an interesting approach to concentrate analyte molecules closer to the metal surface using the swelling effect in PMMA. Using absorption of the analyte, the molecules stay in the gaps between NPs, which is a good solution for one of the biggest challenges in SERS, that is, to guide molecules to the hot spot places.